Achieving both high conductivity and reliable high strength for W–Cu composite alloys using spherical initial powders. (November 2020) - Zhuo, Longchao; Zhang, Junlu; Zhang, Qiqi; Wang, Hailiang; Zhao, Zhao; Chen, Qiuyu; Liang, Shuhua; Xu, Jintao; Xi, Aiying
Abstract: By virtue of spherical initial powders, novel W–Cu composite alloys of W60Cu40 and W70Cu30 have been fabricated by successive processes of powder mixing, cold pressing, sintering and infiltration under hydrogen atmosphere in this work. The phase composition and distribution, hardness, electrical conductivity and tensile behavior of the resultant composite alloys were investigated. Results revealed that the resultant W–Cu composite alloys exhibited excellent hardness improved by 7.3% (4.6%) and remarkably improved electrical conductivity by 23.3% (23.8%), compared with present commercial alloys. Further tensile tests revealed the superior strength of 423 MPa (485 MPa) with reliable strain of 8.8% (7.6%), which can be ascribed to the homogenous structure with alternate soft/conductive Cu and hard W phases free from blind holes. Highlights: Novel W60Cu40 and W70Cu30 composites were made using spherical powders. The composites exhibited highly improved HB by 4.6–7.3%. The composites exhibited remarkably improved conductivity by 23.3–23.8%. The composites exhibited superior strength of 422.8–485.1 MPa. Reliable tensile strain of 7.6% 8.8% was achieved for each composite.